Development of Learning Videos Using Videoscribe Tools in Statistics Learning at Junior High School of Muhammadiyah Koba - Elvira Anjelia; I Nyoman Arcana; Betty Kusumaningrum (Universitas Sarjanawiyata Tamansiswa, 2022)
Advances in Information and Communication Technology (ICT) have been used in the manufacture of learning media for various subjects. This study aims to develop a mathematics learning video using the YouTube-based VideoScribe application on statistics material for class VIII SMP and test the feasibility of the developed learning video. The research method used is the Research and Development method with the ADDIE model, namely Analysis (analysis), Design (product design), Development (product development), Implementation (implementation), and Evaluation (evaluation). The subjects of this study were 20 students of class VIII SMP Muhammadiyah Koba. The data collection instruments used in this study were media validation questionnaires (YouTube learning), student response questionnaires, and learning outcomes tests (THB). The result of this research is a product in the form of a VideoScribe-based learning video which is then uploaded to YouTube which is valid, practical, and effective. The validity test obtained a score of 3.96 with a valid category, field trials obtained a score of 3.67 with a good category and 70% of students met the KKM.